2016
DOI: 10.1016/j.abb.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The biological inorganic chemistry of zinc ions

Abstract: The solution and complexation chemistry of zinc ions is the basis for zinc biology. In living organisms, zinc is redox-inert and has only one valence state: Zn(II). Its coordination environment in proteins is limited by oxygen, nitrogen, and sulfur donors from the side chains of a few amino acids. In an estimated 10% of all human proteins, zinc has a catalytic or structural function and remains bound during the lifetime of the protein. However, in other proteins zinc ions bind reversibly with dissociation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
356
5
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 580 publications
(399 citation statements)
references
References 137 publications
8
356
5
4
Order By: Relevance
“…S3 and Fig. S4)1526. Both potentiometric and CD titrations of Hk peptides with Zn 2+ indicated that Zn 2+ -mediated dimers (Zn(Hk) 2 ) are formed preferentially at pH 7.4 (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…S3 and Fig. S4)1526. Both potentiometric and CD titrations of Hk peptides with Zn 2+ indicated that Zn 2+ -mediated dimers (Zn(Hk) 2 ) are formed preferentially at pH 7.4 (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…For this we took advantage of the ability of the compound 4-(2-pyridylazo)-resorcinol (PAR) to form a colored 2:1 complex with zinc with high affinity (effective dissociation constant of the Zn(PAR) 2 complex, at pH 7.0, 2.1 x 10 −12 M 2 [17]), which presents an absorption maximum at 492 nm and can be measured spectrophotometrically. In turn, EDTA forms a 1:1 complex with zinc of extremely high affinity: 6 x 10 −14 M at pH 7.0 [18]. Therefore, solutions containing EDTA should compete with PAR for zinc binding, in such a way that the decrease in the absorption at 492 nm measured at the equilibrium can be used to infer the concentration of EDTA present in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Below we turn to recent work that points to the need for careful controls in the application of these molecules and the importance of understanding of the underlying chemistry that allows these molecules to detect Zn 2+ . We also refer the reader to an excellent recent review that discusses the complex solution chemistry and speciation of zinc ions in biological environments [5]…”
Section: Probes and Sensorsmentioning
confidence: 99%
“…Mammalian cells maintain a total concentration of Zn 2+ in the hundreds of micromolar [4]. While most of this Zn 2+ is bound to proteins and inaccessible, a pool of labile Zn 2+ , which is non-protein bound and complexed to a variety of small molecule ligands [5], has been detected in the cytosol with a concentration in the hundreds of picomolar. Furthermore, there is growing evidence of a labile Zn 2+ pool in organelles [4, 6].…”
Section: Introductionmentioning
confidence: 99%